The Influence of the Problem-Based Learning Model with a Differentiated Approach on Senior High School Students' Problem-Solving Ability in the Concept of Sound Waves - Siti Fazria Tobuto; Dewa Gede Eka Setiawan; Lukman Samatowa (Universitas Muhammadiyah Palu, 2025)
Problem-solving skills are important skills in physics learning. However, learning practices in schools are still dominated by conventional methods that are less able to accommodate differences in learning styles and student readiness levels. Therefore, the application of the Problem Based Learning (PBL) model with a differentiated approach is seen as effective in improving students' critical, creative, and analytical thinking skills, especially in sound wave materials. This study uses a quantitative method with a quasi-experiment design. The subject of the study was grade XI students of SMA Negeri 1 Kabila which consisted of one experimental class and two replication classes. The research instrument is in the form of pretest and posttest essay questions to measure problem-solving skills. Data analysis was carried out through Liliefors normality test, Alpha Cronbach reliability, paired sample t-test, and N-Gain calculation. The results of the study showed a significant increase in the average pretest and posttest scores in all classes. The normality test states that the data is normally distributed, while the reliability test confirms that the instrument is classified as reliable. The hypothesis test proved that H? was rejected, with an average N-Gain of more than 0.7 which meant a very high increase. Thus, the application of the differentiated PBL model has been proven to have a positive effect on problem-solving skills and encourage students to be more active, involved, motivated, and able to solve contextual problems according to learning styles.